1976
DOI: 10.1007/bf02363557
|View full text |Cite
|
Sign up to set email alerts
|

Transcoronary intravascular transport functions obtained via a stable deconvolution technique

Abstract: Following left atrial injection of indocyanine green in closed-chest, anesthetized dogs, 60 simultaneous input-output pairs of dilution curves were sampled via identical catheter sampling systems from the aortic root, C in (t), and the coronary sinus, C out (t). Assuming that C out (t) was the convolution of a transport function, h(t), and C in (t), a new deconvolution technique was used to solve for the h(t)'s which was not sensitive to noise, recirculation, or the form of h(t).The 60 transcoronary h(t)'s wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0
4

Year Published

1977
1977
1995
1995

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 19 publications
5
20
0
4
Order By: Relevance
“…Similarity has been demonstrated for transorgan transport functions in the kidney by Gomez et al, 22 in the lung over a very limited range of alveolar and left atrial pressures by Knopp and Bassingthwaighte,23 and in the coronary bed by Knopp et al 17 Data from the latter study are plotted in Fig. 11, showing a fair degree of similarity.…”
Section: Tests For Similarity Of Washout Curves At Different Flowssupporting
confidence: 70%
See 3 more Smart Citations
“…Similarity has been demonstrated for transorgan transport functions in the kidney by Gomez et al, 22 in the lung over a very limited range of alveolar and left atrial pressures by Knopp and Bassingthwaighte,23 and in the coronary bed by Knopp et al 17 Data from the latter study are plotted in Fig. 11, showing a fair degree of similarity.…”
Section: Tests For Similarity Of Washout Curves At Different Flowssupporting
confidence: 70%
“…This can probably be done with reasonable accuracy, since the shapes of the impulse responses of the coronary vascular bed have not been shown to differ greatly from shapes that could be fitted with an exponential downslope. 17 However, even though the extrapolation may be adequate, this technique does not provide accurate estimates of coronary blood flow from intracoronary artery injections. There are very limited circumstances under which one can use this impulse injection technique for the estimation of total coronary blood flow.…”
Section: Estimation Of Blood Flowmentioning
confidence: 99%
See 2 more Smart Citations
“…When tracers are injected into the left atrial cavity and flow downstream to enter the coronary arteries, the concentration-time curve for the entering tracer is spread over several seconds, because of dispersion due to the force of injection and the mixing that occurs in the atrium and ventricle. Using 0.5 s left atrial injections, Knopp et al (1976) observed that dye dilution curves obtained in the root of the aorta had a spread of 4 -10 s depending on the flow. Even with left ventricular injections and high speed sampling, Bassingthwaighte and Ackerman (1967) observed similar spreads.…”
Section: Introductionmentioning
confidence: 99%